2021
DOI: 10.23937/2377-4630/1410122
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Anesthesia: Much More Than Single Shot of Hyperbaric Bupivacaine

Abstract: There is significant and renewed attentiveness in the use of regional anesthesia techniques for many common surgeries. The vast majority of anesthesiologists world wide use the routinely the hyperbaric solution of bupivacaine for almost all types of surgery. However, they ignore that spinal anesthesia has more to offer. A different kind of technique for a different kind of patients. The understanding of spinal anesthesia in relation to sensory and motor blocks with hyperbaric and isobaric solutions is shown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…6 However, it was discussed previously that most anesthesiologists prefer to use the sitting position and 0.5% hyperbaric bupivacaine, demonstrating that spinal anesthesia is much more than the use of this position and this solution. 5 In this article it was demonstrated that the new approach with US in all books and articles prefer the sitting position for the neuraxial approach and spinal anesthesia. 5 This fact demonstrates that the use of US also needs to evolve to perform spinal anesthesia in different puncture positions and different local anesthetic solutions (hyperbaric, isobaric, and hypobaric).…”
Section: Local Anesthetic Solutions and Puncture Positionmentioning
confidence: 97%
See 3 more Smart Citations
“…6 However, it was discussed previously that most anesthesiologists prefer to use the sitting position and 0.5% hyperbaric bupivacaine, demonstrating that spinal anesthesia is much more than the use of this position and this solution. 5 In this article it was demonstrated that the new approach with US in all books and articles prefer the sitting position for the neuraxial approach and spinal anesthesia. 5 This fact demonstrates that the use of US also needs to evolve to perform spinal anesthesia in different puncture positions and different local anesthetic solutions (hyperbaric, isobaric, and hypobaric).…”
Section: Local Anesthetic Solutions and Puncture Positionmentioning
confidence: 97%
“…5 In this article it was demonstrated that the new approach with US in all books and articles prefer the sitting position for the neuraxial approach and spinal anesthesia. 5 This fact demonstrates that the use of US also needs to evolve to perform spinal anesthesia in different puncture positions and different local anesthetic solutions (hyperbaric, isobaric, and hypobaric). 5 Likewise, anesthesiologists need to understand the safety of thoracic spinal anesthesia and its puncture positions, and the local anesthetic solutions used, to increase your possibilities for performing spinal anesthesia safely.…”
Section: Local Anesthetic Solutions and Puncture Positionmentioning
confidence: 97%
See 2 more Smart Citations
“…3 In a recent article, we showed that spinal anesthesia is much more than the use of a single injection of hyperbaric bupivacaine. 4 There are several techniques for treating varicose veins. [1][2][3] Being the most serious and operated on in the SUS system, they normally require anesthesia, with spinal anesthesia being the most used.…”
Section: Meaningmentioning
confidence: 99%